The political mobilities of reporting: tethering, slickness and asylum control. Issue 5 (3rd September 2019) - Fisher, Daniel X.O.; Burridge, Andrew; Gill, Nick
ABSTRACT: This paper focuses on the coerced mobilities associated with reporting, meaning the mandatory requirement to regularly check-in with authorities for the purpose of control. Drawing on recent calls for a politics of mobility and advances in carceral geographies, we attend to the forces, movements, speeds and affective materialities of reporting with a focus on deportable migrants and the UK Home Office. In doing so we develop two conceptual lenses through which to further understand the politics of mobility. First, we develop the concept of 'slickness' in the context of the process of becoming detained at a reporting event. We understand slickness as a property of bodies and objects that makes them easier to move. Second, we argue that reporting functions to 'tether' deportable migrants; thereby not only fixing them in place, but also forcing the expenditure of energy and the experience of punishment. The result is that reporting blurs the distinction between detention and 'freedom' by enacting the carceral in everyday spaces.